2020
DOI: 10.1519/jsc.0000000000003662
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Contractile Properties of Knee Joint Muscles Measured by the Method of Tensiomyography in Differently Trained Men and Women

Abstract: Toskić, LD, Dopsaj, MJ, Marković, MR, Toskić, DR, Ignjatović, AM. Mechanical and contractile properties of knee joint muscles measured by the method of tensiomyography in differently trained men and women. J Strength Cond Res 36(6): 1532–1539, 2022—The aim of this study was to investigate the differences in mechanical and contractile properties of knee joint flexor and extensor muscles between differently trained men and women, using tensiomyography (TMG). The sample consisted of 159 subjects (84 men and 75 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
0
9
0
2
Order By: Relevance
“…Because of the higher BF Dm, Tc, and Td in women seen in the current study, our sample seems to align most closely with athlete populations. Specifically, examination of the descriptive values from Toskić et al (37) revealed that our sample of self-reported strong men (1RM back squat: body mass $1.75) and women (1RM back squat:body mass $1.5) had BF Dm and Td values that most closely aligned with the strength and power athletes and BF Tc values most similar to the endurance athletes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Because of the higher BF Dm, Tc, and Td in women seen in the current study, our sample seems to align most closely with athlete populations. Specifically, examination of the descriptive values from Toskić et al (37) revealed that our sample of self-reported strong men (1RM back squat: body mass $1.75) and women (1RM back squat:body mass $1.5) had BF Dm and Td values that most closely aligned with the strength and power athletes and BF Tc values most similar to the endurance athletes.…”
Section: Discussionmentioning
confidence: 76%
“…Of the literature in which direct comparisons can be made based on muscle(s) assessed and parameter(s) examined, researchers have assessed physically active nonathlete, physically inactive nonathlete, and athlete populations. Heterogeneity in nonathletes lead to potentially equivocal differences in men and women (16,24,35,37), although researchers have noted women to have significantly higher BF Dm (22,31), Tc (31), Td (37), and Vc (37) in elite basketball, handball, and volleyball athletes. By contrast, Loturco et al (19) primarily found trivial or small sexbased effect sizes in Vc of the BF and RF of elite track and field jumpers and sprinters, although these researchers calculated Vc at multiple electrical amplitudes.…”
Section: Discussionmentioning
confidence: 99%
“… Toskić et al (2022) showed a higher muscle responsiveness, meaning lower values for T d , in physically active compared to physically inactive people. However, the parameter delay time has rarely been investigated in intervention studies.…”
Section: Discussionmentioning
confidence: 85%
“…Top-level karateka’s agonist muscles (VL, VM and RF) Td, Tc and Tct are found to be different than in the control group. The habituation to ballistic exercises in these athletes has most probably induced specific neuromuscular changes in muscle responsiveness [ 45 ]. The examined VL and VM muscles are extensors in the knee joint [ 46 ], while the RF is an extensor in the knee and also a flexor in the hip joint [ 47 ].…”
Section: Discussionmentioning
confidence: 99%